COGNITIVE AND COMMUNICATIVE FACTORS SHAPING LINGUODIDACTIC COMPETENCE IN CONTEMPORARY LANGUAGE EDUCATION - Khalifa Daribaevna Paluanova (Bright Mind Publishing, 2025)
This article examines the development of linguodidactic competence through the interaction of cognitive and communicative factors in modern language education. Drawing on current research in applied linguistics, psycholinguistics, and educational methodology, the study argues that effective linguodidactic competence depends on the integration of several components: knowledge of language systems, understanding of cognitive mechanisms underlying acquisition, awareness of sociocultural context, and mastery of interactive pedagogical strategies. The article discusses how instructors’ ability to anticipate learning difficulties, design scaffolded activities, and facilitate meaningful communication contributes to improved learner outcomes. Particular attention is given to the role of metalinguistic awareness, task-based instruction, multimodal resources, and technology-enhanced environments in forming a comprehensive linguodidactic skill set. The study concludes that linguodidactic competence should be viewed as a dynamic construct shaped by reflective practice, interdisciplinary knowledge, and continuous professional development, making it essential for high-quality language pedagogy.
Keywords: Linguodidactics, language pedagogy, linguodidactic competence, cognitive factors, communicative approach, language acquisition, instructional design, metalinguistic awareness, teacher development.